Pengaruh Profitabilitas, Solvabilitas, Price Earnings Ratio Dan Price To Book Value Terhadap Return Saham(Studi Empiris pada Perusahaan Makanan dan Minuman Kategori Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2013) - Fatnamasari, Prastika; , Drs. Suyatmin Waskito Adi, M.Si (2016)
This study purposes to examine the effect of profitability proxy by the Return On Assets (ROA), solvency proxy by the Debt to Equity Ratio (DER), the price earnings ratio (PER) and price to book value (PBV) of the stock retrun 2009-2013. The population used in this study food and beverage companies the consumer goods industry category listed in Indonesia Stock Exchange (BEI) in 2009-2013. The data used in this research is secondary data. Methods of sample return with a purposive sampling according to criteria that have been determined. The number of samples collected as many as 75 companies. The analysis was made by using multiple linear regression. These results indicated that (1) Return On Assets (ROA) had a significant affect on the stock returns ; (2) Debt Equity Ratio (DER) has no effect on the stock return ; (3) Price Earnings Ratio (PER) has no effect on the stocks return. This means that the high and low ROA, and PBV can affect the level of stocks return.